ASESMEN RISIKO PERDARAHAN SEKELOMPOK PASIEN FIBRILASI ATRIUM PENERIMA WARFARIN BERDASARKAN NILAI HAS-BLED DI RS ABC GIANYAR - Putu Dian Marani Kurnianta; Ni Komang Putri Pradnyani; Kadek Dwi Oktariadi; Anak Agung Ngurah Putra Riana Prasetya (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
In the management of atrial fibrillation (AF) preventing risk of stroke, warfarin may be prescribed. Warfarin’s narrow therapeutic index encourages the importance of regular monitoring during therapy to avoid the risk of bleeding. This study aimed to describe the risk of bleeding in a group of patients with AF receiving warfarin based on HAS-BLED score assessment at ABC Hospital Gianyar, Bali. A descriptive-observational study was conducted under retrospective case study approach involving outpatient’s data at mentioned hospital. This study included all patients with AF receiving warfarin based on visit history during January 2022-May 2023. Risk of bleeding documentation addressed the HAS-BLED assessment which then were illustrated into tables and diagram according to patients’ profile. From a total of eight eligible patients, five patients (62.5%) had moderate-risk of bleeding (score 1-2) and the rest were in the low-risk category (score 0). Advanced age >65 y.o. (50.00%), use of specified drugs (25.00%), and high INR values had contributed to the findings of moderate-risk based on stratification category. Despite the absence of high-risk category, therapeutic monitoring is necessary focusing on modifiable risk factors. The limited number of samples and several laboratory parameters may suggest for the advancement of clinical practice and further research.